2021
DOI: 10.37506/ijfmt.v15i3.15726
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Tobacco Use among Adolescents and Young Adults in Indonesia: An Analysis of IFLS-5 Data

Diyan Effendi,
Arief Priyo Nugroho,
Zainul Khaqiqi Nantabah
et al.

Abstract: Background:The danger of tobacco use to health has been globally known. However, its prevalence especially in developing countries including Indonesia remains high.This study aims to investigate determinants of tobacco use among adolescents and young adults in Indonesia. These age groups are essential since most regular smokers initiated to smoke at these ages. Methods: This study utilized IFLS wave 5 data. A total of 7213 responses on tobacco use from respondents age 15-24 years old were taken into analysis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 22 publications
2
6
0
Order By: Relevance
“…The older age group (20-24 years) was shown to have a statistically significant positive association with tobacco consumption compared to the 15-19 age group. This finding is consistent with the previous studies on the young population in Indonesia and Nepal, which showed that the 20-24 age group had a higher smoking proportion [6], [24], [25]. This study's finding also confirms the 2014 Indonesia Global Youth Tobacco Survey results that found higher tobacco use prevalence among respondents aged 20-24 years compared to the 15-19 age group [7].…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…The older age group (20-24 years) was shown to have a statistically significant positive association with tobacco consumption compared to the 15-19 age group. This finding is consistent with the previous studies on the young population in Indonesia and Nepal, which showed that the 20-24 age group had a higher smoking proportion [6], [24], [25]. This study's finding also confirms the 2014 Indonesia Global Youth Tobacco Survey results that found higher tobacco use prevalence among respondents aged 20-24 years compared to the 15-19 age group [7].…”
Section: Discussionsupporting
confidence: 92%
“…Sharing cigarettes are also seen as a symbol of solidarity among young males in Indonesia. Further, for a young male, peer influence is fundamental, and thus when he has smoking friends, it will be difficult for him to stop smoking [6].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations